EDUKASI PERLINDUNGAN DIRI DAN LITERASI DIGITAL BAGI ANAK DI KOMPLEKS KOKODA KOTA SORONG - Adolfina Putnarubun,; Leidy Damima,; Tia Metanfanuan,; Bentelina Rut Fiay,; Roberto Kariabe, (Nusantara Hasana Journal, 2026)
Children are a vulnerable group facing various social threats including sexual abuse and the negative impacts of digital technology. Limited understanding of self‑protection and responsible technology use increases the risk of violence and exposure to inappropriate content. This study aims to analyze the implementation of self‑protection and digital literacy education for children in the Kokoda Complex, Sorong City. This research used a descriptive approach through participatory socialization and training methods. The activities were conducted through presentations, interactive discussions, educational games, and quizzes. The results show that interactive learning approaches improve children's understanding of private body parts, encourage them to say 'no' to inappropriate actions, and increase awareness of responsible technology use. Therefore, continuous education regarding self‑protection and digital literacy is essential to support child protection in the digital era.